THE DIFFERENCESS OF DISCONTINUITAS IUD IN POST PLACENTAL AND INTRA-CESAREAN IN MADIUN - Melynda Trilamsari Putri; Ashon Sa'adi; Ivon Diah Wittiarika; Gadis Meinarsari (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: Intra Uterine Device (IUD) which is placed after delivery of the placenta is an attempt to reduce the rate of population growth. However, the achievement is still very low, especially in the post-placental IUD insertion. It is this high expulsion rate that continues to be a concern for service providers, so this method is acceptable. The purpose of this study is to compare the sustainability of IUD acceptors in post-placental and intra-cesareann placement. Methods: The design of this study was cross sectional with an observational analytic method. Location of this research in the family planning clinic of Dr. Soedono Madiun Hospital, Banjarejo Health Center, Tawangrejo Health Center, and PMB Ny. “P” Madiun City in 2019.The sample used consecutive sampling as many as 114 acceptors. The independent variable was the time of IUD insertion. The dependent variable is the discontinuity of the IUD acceptor. The instrument used was the 2019 IUD acceptor medical record. The Fisher Exact Test on SPSS was used to perform data analysis. Results: From 114 acceptors, there was no difference in the discontinuity of IUD acceptors in post-placental and intra-cesarean placement (p=0.1). The incidence of expulsion was found in post-placental insertion (p=0.02). In intra-cesarean IUD acceptors more confirmed using ultrasound examination (p = 0.03). There was no perforation in both. Conclusion: There is no difference in IUD acceptor discontinuity in post-placental and intra-cesarean placement.